PENGARUH PENYULUHAN DENGAN MEDIA LEMBAR BALIK TERHADAP PENINGKATAN PENGETAHUAN TENTANG ANEMIA PADA REMAJA PUTRI SEBAGAI UPAYA PENCEGAHAN STUNTING SEJAK DINI - Permatasari, Agustin Shinta; Lestari, Muji; Wahyuni, Sri (NHM PRESS, 2024)
More than 25% of teenagers suffer from anemia which can have an impact on delayed physical growth, behavioral and emotional disorders which can affect the process of growth and development of brain cells which can reduce body endurance, make them easily weak and hungry, disrupt learning concentration and lack of productivity. Anemia that occurs in adolescence can continue into adulthood, which can contribute greatly to maternal and infant mortality rates, babies born prematurely, LBW, and have an impact on the risk of having toddlers with stunting. The aim of this research was to determine the effect of counseling using flip-sheet media about preventing anemia in adolescent girls on the level of knowledge of adolescent girls. The research design used was Quasi Experiment with One Group PreTest and Posttest Design. The population of this study were all young women at the Health Polytechnic of the Ministry of Health, Jayapura, D3 Midwifery Study Program, semester 2, get 37 respondents taken using a simple purposive sampling technique. The results of this study show that there is an influence of counseling using flip-sheet media on increasing adolescent girls' knowledge about anemia (ρ value=0.000). It is recommended that this flip sheet can be used as a reference for health promotion learning media during counseling for young women. So it is hoped that early prevention of stunting in teenagers can be done by preventing anemia in teenagers.